160k views
15 votes
Solve the following simultaneous equations: 1. a) x-y=-5 and x + y = -1​

User Anindya
by
5.2k points

2 Answers

1 vote

Answer:

x = -3, y = 2

Explanation:

x - y = -5

x = -5 + y

Let's put this into the other equation

(-5 + y) + y = -1

-5 + 2y = -1

2y = 4

y = 2

Now we can solve for x by plugging y into either equation

x + (2) = -1

x = -3

User Sheunis
by
6.3k points
8 votes

Answer:

(x, y) = (-3, 2)

Explanation:

The two equations are recognizable as expressing the sum and difference of the two variables. Such a set of equations is easily solved by the "elimination" method.

__

eliminate y

The y-variables have opposite coefficients in the two equations, so that variable can be eliminated by adding the two equations:

(x -y) +(x +y) = (-5) +(-1)

2x = -6 . . . . . . . simplify

x = -3 . . . . . . divide by 2

eliminate x

The x-variables have the same coefficient in the two equations, so that variable can be eliminated by subtracting one equation from the other. We choose to subtract the first equation so the result has a positive coefficient for y.

(x +y) -(x -y) = (-1) -(-5)

2y = 4 . . . . . . . simplify

y = 2 . . . . . . divide by 2

The solution to the system of equations is (x, y) = (-3, 2).

User DanielCollier
by
5.7k points